Pemberdayaan Karyawan Terhadap Kepuasan Kerja Karyawan Pada PT Rotella Persada Mandiri Lubuk Pakam - Dewi Kartika Lestari; Horia Siregar (ARBITRASE: Journal of Economics and Accounting, 2021)
This research aims to determine the influence of Employee Empowerment toward Employee Satisfaction at PT. Rotella Persada Mandiri Lubuk Pakam. The type of this research was quantitative research. The population in this study were all employees of PT. Rotella Persada Mandiri Lubuk Pakam with 45 employees and a saturation sampling was applied in this study with 45 employees. The data is processed with SPSS 20.0 for windows program. The data analysis technique  was a simple Linear Regression, with the formula Y = a+bX+e. A simple linear regression test result obtained was equation Y = 19,532 + 0.546 X + e, it means the employee empowerment has a significant influence on employee job satisfaction. The results of the t hypothesis test obtained that the value of tobserved > ttable = 4,215 > 2,017. Therefore, the value of tobserved was greater than the ttable hence the hypothesis was accepted. Thus, it can be concluded that the hypothesis stating variable (X) has been proven or in other words there is a significant influence between variable (X) to variable (Y). And based on the determination coefficient test (KD) or R Square (R2) then it can be known that the value of R Square is 0.292 or with a percentage of 29.2 % while the remaining 70.8% is influenced by other variables that are not studied by researchers.